FINANCIAL LITERACY, POLICIES AND REGULATIONS, INFRASTRUCTURE FACILITIES AND FINANCIAL INCLUSION FOR MICRO, SMALL, AND MEDIUM BUSINESS OWNERS - Zumalia; Suhardi; Firdaus, Rahmad; Sri Rejeki, Nadia (Penerbit Lafadz Jaya, 2025)
This study examines the influence of Financial Literacy on Financial Inclusion by considering the role of Infrastructural Facility and Policy and Regulation as mediation variables. The study was conducted on MSMEs in the city of Pangkalpinang with 224 respondents, Data collection was carried out by distributing questionnaires online using Google Forms. The results of the analysis show that Financial Literacy has a significant effect on Financial Inclusion, both directly and through the Infrastructural Facility. On the other hand, mediation through Policy and Regulation is not significant, indicating that political regulation has not played an optimal role in increasing financial inclusion. These findings emphasize the importance of encouraging investment in strengthening infrastructure such as fintech networks and banking services in remote areas as an effective strategy in encouraging wider access to finance. In addition, regulations related to political and financial policies need to be evaluated to be more adaptive and effective in supporting people's financial literacy and access. More applicable financial education programs also need to be expanded through cooperation between the government, the private sector, and MSMEs to increase public understanding and participation in the formal financial system. Further research is suggested to explore additional factors and use a longitudinal approach to gain a more comprehensive understanding.